Impact of Drilling in Embankment Dams : A Comparative study between Water Powered DTH Hammer Drilling Technology and Hydraulic Top Hammer Drills - Riechers, Jörg (2012)
Large geotechnical structures such as embankment dams and tailings dams are subject to high safety requirements. One of the key requirements is long-term stability in order to avoid incidents and failures as well as to ensure environmental safety during and after the operational phases. To ensure security, the instrumentation of existing embankment dams and tailings dams, using drilling technologies, is necessary for surveillance. Drilling in the structures of dams or in their foundations, however, always entails certain risks. Therefore, the selection of drilling technologies must be carried out carefully, taking into account the condition and sensitivity of each dam section. A continuous evaluation and development of existing drilling requirements is an important safety aspect.The main objective of this comparative study, implemented in collaboration between LKAB, Wassara AB, Sweco Infrastructure AB and Luleå University of Technology in Malmberget, Sweden, is to analyse the influence on surrounding soil of a water powered DTH hammer system and top hammer drillings with different setups during the drilling process. Covering an area of 800 m², an artificial dam with a height of 3 m was built and compacted in layers. The soil used was characterised as gravelly sand. Drillings were done vertical and inclined. Weight sounding tests before and after drilling, excavation of boreholes as well as soil sampling for further laboratory analysis have all been conducted. Complementing this research project, one vertical borehole with a depth of 30 m has been drilled with Wassara’s Lost Hammer concept (LHC) in the tailings dam of LKAB in Malmberget.This study concludes by stating that, for the analysed drilling formation, the average radius of influence on soil was identical (0.49 m along the borehole axis) for both the water powered DTH and the hydraulic top hammer system with a pre-drilling protective casing. Top hammer drillings in combination with a casing drilling system (Symmetrix) indicate an increased average zone of ...